At What Dose Can Total Body and Whole Abdominal Irradiation Cause Lethal Intestinal Injury Among C57BL/6J Mice?. Issue 3 (7th September 2020) - Gu, Jia; Chen, Yu-Zhong; Zhang, Zi-Xiang; Yang, Zai-Xing; Duan, Guang-Xin; Qin, Li-Qiang; Zhao, Lin; Xu, Jia-Ying
Purpose and Methods: To investigate the doses of total body (TBI) and whole abdominal irradiation (WAI) induced lethal intestinal injury, healthy C57BL/6 J mice were divided randomly into 7 groups: control group; 6, 7, and 8 Gy TBI groups; and 5, 10, and 15 Gy WAI groups. The survival length, general conditions, body weight, daily food and water intake of the mice and the histopathological changes of small intestine were observed. Results: Lethal injury among C57BL/6 J mice was caused by ≥6 Gy TBI and 15 Gy WAI. Their body weight and food intake decreased, the structure of their small intestinal villi was destroyed, and the number of surviving crypts per circumference of the jejunum decreased in ≥6 Gy TBI groups and 15 Gy WAI group. The mice in the 10 Gy WAI group significantly lost weight within 5 days but recovered slowly thereafter. They also had poor appetite and reversibly damaged intestinal mucosa. Conclusions: Nonlethal intestinal injury could be induced by 10 Gy WAI, whereas lethal intestinal injury could be triggered by ≥6 Gy TBI and >15 Gy WAI in mice. Our results provided a basis for establishing radiation-induced intestinal injury models with C57BL/6 J mice.